Identifying and Evaluating the Components of Human Resource Competence in the Era of Digital Transformation - Mahdieh Abidi; Rashid Zolfaghari Zafarani; Masoud Haghighi (مدیریت و چشم انداز آموزش)
AbstractThe aim of the current research is to identify and evaluate the components of human resource competence in the era of digital transformation. According to its purpose, the research method is applicable-developmental; and mixed (qualitative-quantitative) and exploratory in terms of implementation. The statistical population in the qualitative section includes 20 experts and specialists who are knowledgeable about the research topic and specialists in Iran Mobile Communications Company (Part I) selected by purposeful sampling; and in the quantitative part it includes 2112 personnel of Iran Mobile Communications Company (Part I) in Tehran, 325 people were selected as a sample through Cochran's formula. Data collection was done in the qualitative part by using semi-structured interviews; and in the quantitative part by a researcher-made questionnaire. Analysis of the data in the qualitative part was done by means of Delphi coding, and in the quantitative part, SPSS and PLS software were used. The results in the qualitative section showed that the competence of digital managers includes 7 components of individual factors, organizational factors, culture of change, digital attitude, communication factors, leadership and management, and technical and specialized factors. The results in the quantitative section showed that there is a significant correlation between all components. Also, the culture and change management component was given first priority among the components. The results also showed that the research model has the required validity.Extended abstractIntroductionIn organizations where human resources are given more importance, human resources basically seek to acquire new information and practical solutions in order to achieve better productivity and efficiency, and such organizations have the characteristics of dynamism, creativity and growth in order to create effective changes in internal organizational factors, and interact with their social environment. Therefore, managers facing transformations and changes in the organizational structure, including developments such as maturity and development of employees, competition based on competence to attract and use talents, need to replace the new approaches of human resources management. One of the best and most appropriate approaches to achieve this goal is to use the competency approach in human resources management and planning (Babashahi et al, 2021).Therefore, in the era of digital transformation, changing the role of employees requires a new set of competencies to be defined and presented for them to respond to the latest trends that have been formed following transformative technologies (Wade & Obwegeser, 2019). Equipping employees with the new skills required by the digital age is an important challenge for companies around the world; because the transition to the new digital organization has created deep gaps (Guthrie & Meriwether, 2018). Digital transformation in the world of business and governments has highlighted the importance of productivity more than ever (Sage People, 2018). Digital transformation is a dramatic change in the performance of the organization and the country, centered on transformative technologies such as the Internet of Things, cloud computing, mobile applications, social media, virtual and augmented reality, data analytics, artificial intelligence, and blockchain (Westerman et al, 2014). Although the emphasis of digital transformation is on transformative technologies, some researchers believe that successful digital transformation emphasizes issues related to human resources rather than technology (Wigston, 2019; Tabrizi et al, 2018). Therefore, employees are a key group in the organization that must be taken into account for the digital transformation to come to fruition; because if an organization seeks to create an effective customer experience, it must train its employees well and improve their productivity and loyalty (Wride, 2016).Based on the said material, the researcher is trying to answer the question: how is the identification and evaluate of the components of human resource competence in the era of digital transformation?Theoretical FrameworkCompetenceCompetence shows the image of a grown man who has full preparations in every way to do a job. In fact, competence has a kind of system approach to employees, which includes all those traits, characteristics, skills and attitudes related to the effectiveness in performing tasks and responsibilities. The requirements of human resources planning based on competences is, in the first place, a simulation of business goals and strategies, and every company exists with a purpose to be able to make the necessary profit (Mobini, 2022). Digital transformationDigital transformation is a management approach that refers to the growing adoption of digital technologies and tools by the organization in a way that fundamentally transforms internal and external activities and processes (Bonnet & Nandan, 2011). Digital transformation is the acquisition and deployment of digital technologies in such a way that products, business processes, sales channels, or value chains; in other words, business models are redesigned and transformed (Hess et al, 2016).Karamipur (2023) investigated the design of the model of artificial intelligence competencies on organizational performance by considering business-to-business marketing capabilities. The results showed that the mechanisms of artificial intelligence competencies have an effect on business-to-business marketing capabilities and organizational performance, and also the model of artificial intelligence competencies on organizational performance is confirmed by considering the aspect of business-to-business marketing capabilities.Busulwa et al, (2022) addressed "Digital transformation and hospitality management competencies: towards an integrated framework" in their research. This research showed that digital transformation should lead to the creation of competencies such as digital customer interaction, digital customer experience management, digital innovation, and digital leadership in people.Research methodologyAccording to its purpose, the research method is applicable-developmental; and mixed (qualitative-quantitative) and exploratory in terms of implementation. The statistical population in the qualitative section includes 20 experts and specialists who are knowledgeable about the research topic and specialists in Iran Mobile Communications Company (Part I) selected by purposeful sampling; and in the quantitative part it includes 2112 personnel of Iran Mobile Communications Company (Part I) in Tehran, 325 people were selected as a sample through Cochran's formula. Data collection was done in the qualitative part by using semi-structured interviews; and in the quantitative part by a researcher-made questionnaire.Research findingsAnalysis of the data in the qualitative part was done by means of Delphi coding, and in the quantitative part, SPSS and PLS software were used. The results in the qualitative section showed that the competence of digital managers includes 7 components of individual factors, organizational factors, culture of change, digital attitude, communication factors, leadership and management, and technical and specialized factors. The results in the quantitative section showed that there is a significant correlation between all components. Also, the culture and change management component was given first priority among the components. The results also showed that the research model has the required validity.ConclusionThe current research was conducted with the aim of identifying and evaluating the components of human resource competence in the era of digital transformation. The results of this research are in agreement with the results of Karamipur (2023), Busulwa et al, (2022), Shohel et al, (2022), Crawford & Butler (2021), Asgharneghad & Haghdoust (2022), Linde et al, (2021), Gupta et al, (2021), Kaufman et al, (2021), Abedi Ardakani et al, (2022), Ghirtmand & Amiri Moghadam (2021), and Rahmati Kohroodi et al, (2021). Gupta et al, (2021) showed that organizational factors are the most important factors that need immediate attention. Sub-factors that are important for building competencies in the logistics sector are providing the appropriate training in the field of functional skills development, top management support, and commitment to digitization and organizational culture for process digitization, etc.According to the results of this research, the following suggestions are presented:- One of the suggestions that can be made in line with the results of this research is related to individual factors. The results showed that one of the most important personality traits of successful managers is risk taking. In order to increase risk-taking, it is suggested that managers formulate specific and clear goals for themselves and the organization. These goals are designed based on the vision of the organization. For this purpose, it is suggested to first identify the weaknesses and strengths, risks, and situations of the organization by relying on the SWAT analysis, and then examine and compile the organization's prospects.- By in-depth examination of technical and specialized factors for managers to have more mastery of technology-oriented practical concepts, it is suggested that the mobile communication company recruit and select employees who have full dominance on English language. It is also suggested to consider specialized language courses to improve the knowledge and mastery of conversation and understanding of managers' content.